NORDSTAR: paving the way for a new era in asthma research. Issue 4 (2nd April 2020) - Geale, Kirk; Darabi, Hatef; Lindh, Maria; Fues Wahl, Hanna; Ström, Oskar; Cao, Hui; Alvares, Luisa; Dodge, Rikke; Loefroth, Emil; Altraja, Alan; Backer, Vibeke; Backman, Helena; et al.
NORDSTAR is a longitudinal dataset for the study of asthma comprising 3.3 million individuals and over 50 million person-years in 4 Nordic countries. The data include diagnoses, medication dispensing, use of resources and costs, socio-demographics, and mortality. http://bit.ly/2HueyEt